Two-Phase Flow Analysis and Design of Geothermal Energy Turbine. (August 2019) - Rane, S; He, L
Abstract: A two-phase geothermal turbine generates mechanical energy by means of a total flow system. Literature references are available for experimental investigation of such flow machines but there is no validated numerical model for prediction of flow field and flashing for optimal design of the turbine's flow channels. This paper presents a test reaction-turbine design study with two-phase flow using CFD. An Eulerian-Eulerian multiphase model with the Thermal Phase-Change criteria for two-phase heat, mass and momentum transfer has been used. Phase change validation has been conducted on published experimental data on a converging-diverging nozzle flow at various operating conditions. The stationary nozzle model was then extended to curved nozzle turbine and the results of flow and power has been validated with the data available in literature. Liquid water and vapour distribution due to flash evaporation was predicted by the analysis. Two-phase turbine model so established has been used further to re-design and optimise turbine nozzle by evaluating its cross section, area ratio, throat design, specific torque variation and curvature. Two new channel geometries, square and blended, were compared with the base circular channel and it was found that a blended channel offers on an average 6% higher specific power at 4623rpm. For the same rotor diameters and feed water flow rate, the power output could thus be improved by 4.5%. Isentropic efficiency in the range of 10 to 19% was estimated. Final design will be prototyped and tested in the laboratory for validation of design and deployment in eastern Africa.